Non-inferential transitions: imagery and association - Quilty-Dunn, J; Mandelbaum, E (Routledge, 2019)
Unconscious logical inference seems to rely on the syntactic structures of mental representations (Quilty-Dunn and Mandelbaum, 2018). Other transitions, such as transitions using iconic representations and associative transitions, are harder to assimilate to syntax-based theories. Here we tackle these difficulties head on in the interest of a fuller taxonomy of mental transitions. Along the way we discuss how icons can be compositional without having constituent structure, and expand and defend the ‘symmetry condition’ on Associationism (the idea that associative links and transitions are perfectly symmetric). In the end, we show how a BIT (‘bare inferential transition’) theory can cohabitate with these other non-inferential mental transitions.